The Sustainability of Pahang Barat Integrated Agricultural Development Project in Peninsular Malaysia - Bra, Sulog G. (1999)
This study was conducted in six rural villages in the western part of the state of Pahang. The study's general objective was to assess the overall IADP project sustainability through its integrated impact on the environment, economic, and social well being of the beneficiaries and the villages. The specific objectives were to: (i) identify environmental related variables and determine their level of sustainability contribution to IADP; (ii) identify economic related variables and determine their level of sustainability among the beneficiaries; and (iii) identify social related variables and determine their level of sustainability in relation to the beneficiaries transformation, organisation and community practices. Data collected through survey were supported by data collected through observation and document study. The survey elicited perception responses from one hundred eleven respondents selected at random through questionnaire with open ended questions administered by means of interview-schedule. Observation was done on the status of IADP and its sustainable impact on the environment, economic and social practices of the beneficiaries. The documents studied include the IADP progress reports; statistical data on the environmental condition of the project area taken from the Meteorological Services and Department of Environment of Malaysia; nutritional, health and educational aspects from the villages' clinics and schools, respectively. Descriptive statistics such as frequency, percentage, mean and standard deviations were used in describing the results.